Race and religion among the chosen peoples of Crown Heights - Goldschmidt, Henry (Rutgers University Press, 2006)
In the first major scholarly work to look beyond the sensationalized violence of August 1991, Henry Goldschmidt explores the everyday realities of Black-Jewish difference in the Brooklyn neighborhood of Crown Heights. Drawing on two years of ethnographic fieldwork, he argues that collective identities like Blackness and Jewishness are particularly complex in today's Crown Heights because the neighborhood's Afro-Caribbean, African American, and Lubavitch Hasidic communities understand their differences in dramatically different ways--as a racial divide between Blacks and Whites or a religious di.